Instability of Cauchy horizon induced by the graviton mass - Lu Chen; Shun Jiang (Physics Letters B, 2025)
Massive gravitons are typically introduced to address cosmological issues such as dark energy. In the context of considering massless scalar field perturbations in a charged static black hole, our paper explores the impact of graviton mass on the stability of the Cauchy horizon. By employing numerical techniques such as the pseudospectral method, we calculated the quasinormal mode frequencies under various spacetime parameters. The results indicate that even in the absence of a cosmological constant, the mass of the graviton can lead to violations of the strong cosmic censorship (SCC) conjecture for nearly extremal black holes within the classical framework. Additionally, we examined the effects of graviton mass and other parameters on the region of SCC violation, revealing that as the graviton mass increases, the interval of SCC violation correspondingly expands.